Exploring new pathways to enhance high entropy alloys properties - Șerban Beatrice – Adriana; Cursaru Laura – Mădălina; Badea Ioana – Cristina; Piticescu Radu Robert; Pogrebnjak Alexander (MATEC Web of Conferences, 2024)
For decades, conventional alloys represented the main pillar of engineering applications. However, their performances reach the limit when it faces tough demanding environments. High-entropy alloys (HEAs) meet this important challenge by leveraging the concept of entropy to achieve a unique combination of properties. This scientific paper presents the HEAs coatings, exploring their general characteristics and the exciting possibilities they offer, then the focus will be on HEA coatings, analysing their advantages and potential applications. Finally, the discussion will be held on the modelling techniques used to understand and predict the behaviour of these type of alloys.